The question of ordering: creativity and limitation in political communities - Kalpokas, Ignas (2016)
This thesis is an enquiry into political ordering under its four core attributes: the state, sovereignty, law, and politics. It advocates analysing ordering as a process, rather than ‘order’ as a static given, and introduces an interactive model of ordering, which takes into account both the creative and the limiting thrusts in political communities. This thesis is informed by the theories of Benedict Spinoza and Carl Schmitt. The first chapter is dedicated to assessing the current debate around the four core concepts: the state, sovereignty, law, and politics. Although it is not aimed at providing a full and definitive account of the scholarly debate, some major trends in current political and legal thinking are overviewed. This exposition subsequently serves as both the context and the impetus for the dynamic model of ordering, constructed in the final chapter. The following two chapters are dedicated to the theories of Spinoza and Schmitt. In Spinoza’s case, some metaphysical preconditions have to be explored beforehand: immanent causality, striving to persevere in existence, and the right as power doctrine. The thesis then moves to the role of the state, sovereignty, law, and politics as tools for ensuring communal cohesion despite a general lack of reason and for joint progression towards reason. As for Schmitt, the thesis first delves into his emphasis on the fallen nature of humans, based on his religious convictions. The state, sovereignty, law, and politics are then analysed as parts of an effort to establish order where actually there can be none (since human existence is groundless), necessitating order-qua-theology. Thus, Spinoza and Schmitt both oppose and complement each other. Lastly, the final chapter proposes an interactive model of ordering as perpetual process by revisiting the four core elements from a Spinozist-Schmittian perspective. This model postulates ordering as animated by constant tension between and reciprocal reproduction of the constitutive and the constituted thrusts, both of them being creative and limiting in different respects. In this model, groundlessness is seen as the basic condition which is, nevertheless, constantly counterbalanced by a need for quasi-religious belief in a quasi-objective given, e.g. Spinoza’s reason. Communal life is, therefore, constantly caught in-between these two poles. Consequently, ordering-as-process is claimed to be the only way in which anything common can be posited.